Bush v. Gore and the 2000 US presidential election: a case study of the role of courts in political disputes - Shapiro, S (Foundation for Law, Justice and Society, 2009)
The US Supreme Court’s decision in Bush v. Gore, which effectively ended the 2000 presidential election, provoked a profound national debate about the role of the judiciary in resolving political disputes and raised still lingering questions about the Supreme Court’s credibility as a nonpartisan institution. The lesson to be drawn from Bush v. Gore is not that electoral disputes, even presidential election disputes, are beyond judicial competence. Elections are partisan contests governed by what should ideally be nonpartisan rules. Courts have a role in enforcing those rules to ensure a fair election. But courts must exercise that authority carefully and wisely. Bush v. Gore failed that test.